Removal of Fluoride Ions (F-1) from Contaminated Drinking Water using MnFe2O4 /Banana Peels Composite Synthesized through Chemical Co-Precipitation Method - Sajid, Muhammad; Aamir, Muhammad; Jamil, Muhammad; Ahmad, Dr. Mukhtar; Qamar Hussain, Shahzada (Journal of Materials and Physical Sciences, 2022)
Fluoride (F) contaminated water is of immense health risk. Skeletal as well as dental fluorosis is due to the excessive Fluoride (> 1.5 mg/L) concentration in drinking water. In the present work, MnFe2O4 /banana Peels composite a unique adsorbent has been explored for the elimination of fluoride from aqueous system. These nanocomposites were characterized by XRD and FTIR. Retentivity and coercivity value of nanocomposite is determined by Hysteresis loop. The optimized conditions for the removal of 86% fluoride from field water sample was achieved at pH 8 and in 175 min. From the experimental results, it may be inferred that MnFe2O4 /banana peels composite is an adequate adsorbent for the removal of fluoride from water.